Measurement of Low Concentration of Nanosized Objects Suspended in a Liquid Medium - Merkulovs, Dmitrijs; Vilitis, Oskars; Kozlovs, V. (De Gruyter Open Ltd, 2018)
The new optical scheme of refractometer with temperature stabilisation 10-2 °C is developed, which allows measuring a refractive index of the sample with accuracy not worse than 10-5; dependence of refraction index on concentration of SiO2 nanoparticles in liquid suspension is obtained within the framework of the research.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; concentration measurement; nanoparticles; refractive index; suspension